The Lancet Respiratory Medicine Commission: 2019 update: epidemiology, pathogenesis, transmission, diagnosis, and management of multidrug-resistant and incurable tuberculosis. Issue 9 (September 2019) - Dheda, Keertan; Gumbo, Tawanda; Maartens, Gary; Dooley, Kelly E; Murray, Megan; Furin, Jennifer; Nardell, Edward A; Warren, Robin M; ,; Dheda, Keertan; Gumbo, Tawanda; Maartens, Gary; et al.
Summary: The Lancet Respiratory Medicine Commission on drug-resistant tuberculosis was published in 2017, which comprehensively reviewed and provided recommendations on various aspects of the disease. Several key new developments regarding drug-resistant tuberculosis are outlined in this Commission Update. The WHO guidelines on treating drug-resistant tuberculosis were updated in 2019 with a reclassification of second line anti-tuberculosis drugs. An injection-free MDR tuberculosis treatment regimen is now recommended. Over the past 3 years, advances in treatment include the recognition of the safety and mortality benefit of bedaquiline, the finding that the 9–11 month injectable-based 'Bangladesh' regimen was non-inferior to longer regimens, and promising interim results of a novel 6 month 3-drug regimen (bedaquiline, pretomanid, and linezolid). Studies of explanted lungs from patients with drug-resistant tuberculosis have shown substantial drug-specific gradients across pulmonary cavities, suggesting that alternative dosing and drug delivery strategies are needed to reduce functional monotherapy at the site of disease. Several controversies are discussed including the optimal route of drug administration, optimal number of drugs constituting a regimen, selection of individual drugs for a regimen, duration of the regimen, and minimal desirable standards of antibiotic stewardship. Newer rapid nucleic acid amplification test platforms, including point-of-care systems that facilitate active case-finding, are discussed. The rapid diagnosis of resistance to other drugs, (notably fluoroquinolones), and detection of resistance by targeted or whole genome sequencing will probably change the diagnostic landscape in the near future.